1980
DOI: 10.2508/chikusan.51.673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen on Adipose Tissue Accumulation in Chicks, with Reference to Changes in Triglyceride Synthesis and Fatty acid Oxidation

Abstract: Triglyceride synthesis and fatty acid oxidation in chick adipose tissue were studied by measuring the incorporation of [1-14C] acetate or [1-14C] palmitate into triglyceride and CO2 in vivo and in vitro in order to investigate the effect of estrogen on adipose tissue accumulation in chicks. Estrogen treatment increased the incorporation of 14C-acetate into total fatty acid and of 14C -palmitate into triglyceride . This result suggests that de novo triglyceride synthesis is stimulated by estrogen. Incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…When birds are laying, the ovarian follicles secrete estrogen to stimulate liver lipogenesis and to depress the rate of fatty acid β-oxidation. This event obviously enhances plasma TG (Hasegawa et al, 1980b;Leclercq, 1984). This study demonstrated that the activities of liver lipogenesis enzymes of ducks are higher during the laying period than during the growing period.…”
Section: Discussionmentioning
confidence: 62%
“…When birds are laying, the ovarian follicles secrete estrogen to stimulate liver lipogenesis and to depress the rate of fatty acid β-oxidation. This event obviously enhances plasma TG (Hasegawa et al, 1980b;Leclercq, 1984). This study demonstrated that the activities of liver lipogenesis enzymes of ducks are higher during the laying period than during the growing period.…”
Section: Discussionmentioning
confidence: 62%
“…Major factors contributing to the increase in serum triglyceride level may be as follows; (a) enhanced synthesis of triglyceride in the liver, (b) diminished oxidation of fatty acid in the liver, (c) enhanced secretion of triglyceride from the liver into the blood, (d) impaired removal of serum triglyceride by adipose tissue or muscle and (e) the combination of (a), (b), (c) and (d). Since estrogen significantly increased the triglyceride content in adipose tissue and muscle3, 6,8,9), the contribution of factor (d) to the hypertriglyceridemia could be ruled out. Hepatic output of triglyceride was increased by estrogen treatment in chicks and rats35,38) and Weinstein et al31) have reported that the increased rate of secretion of triglyceride by the liver produced by estrogen, regardless of mechanisms, is probably the result of a net increase in the rate of biosynthesis of triglyceride.…”
mentioning
confidence: 99%